Spiritual Leadership in Healthcare: A Systematic Review of Empirical Studies and Research Directions - Naqach, Taha-Yacine (Journal of religion and health, 2026)
This systematic review evaluates the current state of empirical research on spiritual leadership in healthcare, focusing on its antecedents, mediators/moderators, and outcomes. Peer-reviewed English studies published between 2003 and 2023 were identified through systematic searches in Scopus, Web of Science, and PubMed databases. The JBI critical appraisal checklists for cross‑sectional and qualitative studies were used to assess the risk of bias, and the review followed the JBI methodology for mixed-methods systematic reviews, employing a convergent segregated approach for data synthesis and integration. A total of 60 studies were selected, revealing significant associations between spiritual leadership and 37 outcomes. Twelve mediators, including spiritual well-being, influenced 15 outcomes. Additionally, five key antecedents were identified. However, measurement inconsistencies and contextual variations in spiritual leadership definitions were noted. The review underscores the need for further research, particularly longitudinal and interventional studies across diverse healthcare settings, to evaluate the impact of spiritual leadership while considering cultural and religious differences.